Pengaruh Budaya Organisasi Terhadap Produktivitas Kerja Melalui Kepuasan Kerja - Kustinah, Lina (Universitas Negeri Surabaya, 2024)
This study aims to determine and explain the influence of organizational culture on work productivity through job satisfaction in employees. This research is classified as quantitative research with a population of 67 employees, and the sampling technique used purposive sampling with a sample size of 66 employees. The statistical analysis used in this research is Structural Equation Modeling (SEM) with the help of Smart Partial Least Squares (PLS) 3.2.9 software. The results of this study indicate that organizational culture has a significant positive effect on work productivity, organizational culture has a considerable positive impact on job satisfaction, job satisfaction has a significant positive effect on work productivity, job satisfaction can mediate the impact of organizational culture on work productivity. The implications of the results of this study can be applied. This study found that a strong and positively energized organizational culture can increase work productivity through increased employee job satisfaction. The implication of this research on organizational culture is that some company employees feel the need to get training related to digital content creation. Implications regarding job satisfaction, the company needs to build the trust of all employees, by always being responsive in providing clear and precise information related to new policies that apply in the company. Implications regarding work productivity, namely the company needs to conduct a regular inventory of resources to ensure that the needs of employees are met.